2020
DOI: 10.3389/fnut.2020.00122
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake, Body Composition and Iron Status in Experienced and Elite Climbers

Abstract: Climbing has developed into a popular recreational and elite sport, evidenced by a growing number of licenced competition athletes, and the acceptance into the Olympic calendar for Tokyo 2020. A nutritional assessment, including the evaluation of anthropometric and biochemical data, has not been previously reported in climbing athletes. Therefore, the aim of this study was to assess the dietary intake, body composition, and iron status in experienced climbers, across a range of performance levels. Forty climbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 71 publications
(137 reference statements)
5
27
2
Order By: Relevance
“…All the studies with climbers known to us concluded that EI, when compared to predicted energy expenditure (calculated as a product of basal metabolic rate and physical activity factor), was too low in both adolescent and adult climbers (Kemmler, et al, 2006;Merrells, et al, 2008;Sas-Nowosielski & Wycislik, 2019;Zapf, et al, 2001). The only study that determined EA was conducted with adult climbers and the average EA of the participants was 41.4 ± 9 kcal/kg FFM/ day, with significantly higher EA in females than in males (45.6 ± 7 kcal/kg FFM/day vs. 37.2 ± 9 kcal/ kg FFM/day, respectively) (Gibson-Smith, et al, 2020). Further, 78% of elite adult climbers failed to meet the predicted energy requirement to support a moderate level of physical activity with an average of 12 hours of training/week, while 18% failed to meet the predicted RMR values (Gibson-Smith, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All the studies with climbers known to us concluded that EI, when compared to predicted energy expenditure (calculated as a product of basal metabolic rate and physical activity factor), was too low in both adolescent and adult climbers (Kemmler, et al, 2006;Merrells, et al, 2008;Sas-Nowosielski & Wycislik, 2019;Zapf, et al, 2001). The only study that determined EA was conducted with adult climbers and the average EA of the participants was 41.4 ± 9 kcal/kg FFM/ day, with significantly higher EA in females than in males (45.6 ± 7 kcal/kg FFM/day vs. 37.2 ± 9 kcal/ kg FFM/day, respectively) (Gibson-Smith, et al, 2020). Further, 78% of elite adult climbers failed to meet the predicted energy requirement to support a moderate level of physical activity with an average of 12 hours of training/week, while 18% failed to meet the predicted RMR values (Gibson-Smith, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The only study that determined EA was conducted with adult climbers and the average EA of the participants was 41.4 ± 9 kcal/kg FFM/ day, with significantly higher EA in females than in males (45.6 ± 7 kcal/kg FFM/day vs. 37.2 ± 9 kcal/ kg FFM/day, respectively) (Gibson-Smith, et al, 2020). Further, 78% of elite adult climbers failed to meet the predicted energy requirement to support a moderate level of physical activity with an average of 12 hours of training/week, while 18% failed to meet the predicted RMR values (Gibson-Smith, et al, 2020). In our study, EI of as many as 26% of adolescent climbers (four males, three females) failed to meet the predicted BMR, despite the high training load.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Athletes competing in these types of sports have displayed an increased prevalence of disordered eating and chronically low body weight (Sundgot-Borgen and Garthe, 2011 ). Studies assessing eating behavior or nutrient intake among climbers have found disordered eating (Joubert et al, 2020 ), energy restriction (Zapf et al, 2001 ; Michael et al, 2019 ; Sas-Nowosielski and Wycislik, 2019 ), and iron deficiencies (Gibson-Smith et al, 2020 ). Some research indicates no correlation of low BMI and high climbing performance (Grønhaug, 2019 ), yet anecdotal evidence points to a climbing culture that values thinness and often encourages athletes to minimize weight through restrictive eating habits (Leslie-Wujastyk, 2019 ; Lucas, 2021 ).…”
Section: Introductionmentioning
confidence: 99%